Prospective comparative study of extra-articular distal tibia fractures-intramedullary nailing versus medial minimally invasive percutaneous plating - Lakhotia, Devendra; Meena, Ashok; Bishnoi, Madharam; Sharma, Kartikeya; Shinde, Padmakar (International Journal of Research in Orthopaedics, 2020)
Background: The distal tibia extra-articular fractures are treated with both intramedullary nailing (IMN) and medial minimally invasive percutaneous plate osteosynthesis (MIPPO). The aim of this study was to compare the results of IMN and medial MIPPO in distal tibia fractures. The complications and secondary interventions in both groups were compared. Methods: Fifty patients with distal tibia were randomly assigned to IMN (group 1) and medial MIPPO group (group 2). The functional outcomes were evaluated using American Orthopaedic Foot and Ankle Society (AOFAS) score. Complications like infection, delayed union, non-union, malunion, hardware prominence and secondary interventions were compared. Results: The average union time was 21.12±6.93 weeks in group 1 and 23.56±6.96 weeks in group 2 (p=0.220). The mean AOFAS scoring was 90.76±7.9 in group 1 and 88.4±8.33 in group 2 (p=0.339). Five patients in group 1 and one in group 2 had malalignment. Deep infection was present in one and superficial infection was present in two cases in group 2. None of the patients in group 1 had infections. Three patients in group I developed anterior knee pain and six in group 2 had hardware prominence. Seven cases in IMN group required secondary interventions and fourteen in medial MIPPO group. Conclusions: Extra-articular distal tibia fractures are successfully treated with IMN and medial MIPPO with comparable functional outcomes. Prevalence of malunion was higher in IMN group and hardware prominence was more prevalent in MIPPO group. Implant removal are more in medial MIPPO group mostly due to implant irritation.